USING THE LOCAL HERITAGE IN MUSICAL EDUCATION TO PRODUCE CREATIVITY: MOROCCAN CHILD MUSIC AS A MODEL: Received: 01st September 2023; Revised: 27th December 2023, 03rd January 2024; Accepted: 14th September 2023 - Blidi, Omar El (PUPIL: International Journal of Teaching, Education and Learning, 2024)
Nowadays, practical scientific studies penetrate all fields of science to develop and advance them, especially education sciences. From this point of view, and based on the fact that Morocco is striving to achieve progress at the level of its global classification concerning the quality of education and attention giving into its human and immaterial capital, there is a fundamental necessity of adopting a preventive treatment plan based on scientific research to preserve the intangible heritage and its exploitation in the development and construction of the generation of tomorrow's Morocco. This research focuses, through a set of scientific methods, on studying the impact of using the digitized musical heritage of the child in order to influence levels of creativity and academic achievement in primary schools with fragile social and economic backgrounds. A multi-scientific approach was chosen for this study, which embraced creativity under two different perspectives: one of creativity as a product and the other of creativity as a process. The methods used to explore the problem were quantitative, in the form of a standardized test of creativity and analysis of score averages, combined with descriptive observation. The results show a positive correlation between the technical research program and the improvement of creative cognitive skills in the Moroccan primary school. However, the results of the quantitative creativity test left some questions about the relationship of the use of arts in education and academic achievement. Creativity has proven that it can be understood more systematically when examined in the context of the creative process. Finally, the current research has led to several points of discussion and recommendations for future research.